Pelatihan Teknik Merajut terhadap Guru Kelas 1 dan 2 Sekolah Dasar menggunakan Media Pembelajaran berupa Video Tutorial - Dian Rinjani; Maya Purnama Sari; Fahmi Candra Permana (Jurnal Pengabdian Pada Masyarakat, 2020)
KNITTING TECHNIQUE TRAINING FOR CLASS 1 AND 2 ELEMENTARY SCHOOL TEACHERS USING LEARNING MEDIA IN THE FORM OF VIDEO TUTORIALS. In a child's development, patience is needed to train brain development, because one way to stimulate a child’s brain development is by introducing various activities that require accuracy, patience and good hand and eye coordination such as knitting that requires accuracy. Today the problem in knitting is limited human resources. The purpose of community service is to introduce how to knit to children aged 7 and 8 through their teachers at school. With the intention of reaching a wider audience. The method used in the implementation of community service activities is divided into 2 (two), namely the training phase and the assistance stage. During this training, participants will make 2 (two) knitting products in the form of a pencil holder or coin holder and skullcaps. Each knitting product uses a different knitting tool. The purpose of using different tools is so that participants know and can compare which tools are more easily applied to their students. With this skill, participants can provide knitting material for a longer period of time for their students.